Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Turnover Intention Karwayan pada KSP Semarak Dana Mojokerto (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
High turnover intention among employees presents a serious challenge to the sustainability of an organization. Excessive workload and an unfavorable work environment can trigger employees' desire to switch jobs. This study aims to analyze the impact of workload and work environment on turnover intention among employees at KSP Semarak Dana Mojokerto. The objective of this study is to determine how workload and work environment influence turnover intention at the Koperasi Simpan Pinjam (KSP) Semarak Dana Mojokerto. The research uses a quantitative approach with a survey method. Data was collected through questionnaires distributed to all 36 active employees of KSP Semarak Dana Mojokerto. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results show that workload has a positive and significant effect on turnover intention. Similarly, the work environment also has a positive and significant effect on turnover intention. Simultaneously, workload and work environment significantly influence employee turnover intention. These findings suggest that excessive workload, such as demands for customer recruitment targets, delinquency-free collections, timely deposits, and threats of sanctions for unmet targets, can lead to chronic stress, emotional exhaustion, and decreased job satisfaction, ultimately driving the intention to leave the job. Therefore, management needs to manage workloads with a work-life balance approach, fair task distribution, target adjustments based on regional conditions, adequate facilities, and performance evaluations that focus on work quality rather than just quantity. By implementing these strategies, turnover intention can be reduced, and employees can work more optimally and with higher satisfaction.